Effects of supplemental jump and sprint exercise training on sand on athletic performance of male U17 handball players - Hammami, M.; Gaamouri, N.; Ramirez-Campillo, R.; Aloui, G.; Shephard, R. J.; Hill, L.; Knechtle, B.; Chelly, M. S. (International Journal of Sports Science & Coaching, 2022)
This controlled study investigated the effects of 7 weeks pre-season supplemental jump and sprint exercise training on sand (JSETS) on athletic ability in male handball players. Males (n = 40; 16.3 ± 0.4 years) were randomly assigned to a jump and sprint training (JSTG; n = 24) or a control (CG; n = 18) group. The JSETS replaced a part of the regular handball training of players. The tests included jumps (squat, counter-movement, and 5 jump tests), sprint times (5 m, 10 m and 20 m), agility (modified T and modified Illinois tests), repeated sprint T-test, and balance (standing stork and Y balance tests). JSTG showed relative to CG significant decreases in sprint times over all distances (5 m (p = 0.002, d = 0.735 (medium); 10 m (p = 0.012, d = 0.577 (medium) and 20 m (p = 0.012, d = 0.573 (medium)), and gains in both measures of agility (p = 0.001, d = 0.859 (large) and p = 0.004, d = 0.670 (medium) for T-Half and Illinois-tests respectively), and in jumping squat (p < 0.001, d = 0.813 (large)) and countermovement jumping (p = 0.004, d = 0.663 (medium)), but not in the 5-jump test. Three of the four repeated sprint scores (best time (BT), meantime (MT) and total time (TT)) improved significantly (p = 0.012, d = 0.577 (medium); p = 0.042, d = 0.463 (small) and p = 0.043, d = 0.458 (small) respectively), but the decrement (DEC) remained unchanged. The Y balance test showed significant gains in 2 of 3 scores for the right leg and 1 of 3 scores for the left leg, and the stork balance (right leg) was enhanced. In conclusion, compared to regular handball training, supplemental jump and sprint exercise training on sand substantially improved sprinting, agility, jumping, repeated sprinting, and balance in male handball players.